«To do good and love one’s country»: Three Italian poetesses during the Risorgimento - Frasca, Elena (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2023)
It is well known that the Risorgimento provides a vast reservoir from which to draw insights into a social, territorial and political fabric that was undergoing an era-defining transformation. Research into the substantial and significant metamorphosis underway during the period can be approached from various angles, allowing wider conclusions to be drawn. This article will consider an interesting source that had an essential role in the inexorable process of sweeping change that characterised the 1800s: the periodical press. In particular, it focuses on the analysis of a periodical which was founded during a particularly meaningful time period. L’Alba was published in Catania in 1845 as a “strenna”, a gift given to Baron Antonino Ursino Recupero on New Year’s Day of that year. Among the eighty-nine compositions contained in the periodical, the contributions written by three Neapolitan female poets stand out: Laura Beatrice Oliva Mancini, Irene Ricciardi Capecelatro and Maria Giuseppa Guacci. The historical developments around the fate of periodicals, particularly those with political aims, during that part of the nineteenth century are intertwined with the public and personal lives of three women who played a significant role in the evolution of a society undergoing transformation, dedicating themselves to public work related to culture, literature and poetry, without forgetting the attention they gave more to innovative forms of education, moulded by their perspective as women.